A psychometric examination of the PAI-SF in persons with recent stroke. Issue 6 (22nd July 2022) - Udala, Megan; Ohlhauser, Lisa; Campbell, McKenzie; Langlois, Annick; Leitner, Damian; Libben, Maya; Miller, Harry
Abstract: Objective: The present study evaluated the psychometric properties of the Personality Assessment Inventory-Short Form (PAI-SF) for use with patients with recent stroke. Method: Study participants ( N = 170) were inpatients in a tertiary hospital in Western Canada admitted to a rehabilitation department who completed a neuropsychological evaluation as part of their care. All participants completed the full-form of the PAI (344 items) and both full- and short-form (160 items) versions were scored from the same protocol. Results: Internal consistency for the PAI-SF scales was assessed by Cronbach's coefficient alpha. Alpha coefficients for clinical scales fell between the range of 0.53 (ANT) to 0.88 (ANX), with three scales (ANT, ALC, and DRG) falling below satisfactory (<0.70). Alpha coefficients were unsatisfactory for validity, treatment, and interpersonal scales. Absolute differences between mean clinical scale t scores between the full and short-form PAI clinical scales ranged from 0.04 (DEP) to 1.18 (MAN). For an individual, absolute differences in scale t scores between the full- and short-forms ranged from 0 to 30 t scores. On average, an individual varied 3.75 t scores between the PAI full- and short-form across all validity, clinical, interpersonal, and treatment scales. Component structure was similar across the full- and short-forms. Conclusions: Findings are somewhat consistent with previous literature on the PAI-SF as the full- and short-forms had minimal differences and similar psychometric properties. However, caution is warranted for the clinical utility for both forms given the lower alpha coefficients and different structure. Only certain clinical scales appear to have strong psychometric properties.